PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN MELALUI KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Zulfa Afifatul Azhar; Andi Wijayanto (Universitas Diponegoro, 2018)
This study aims to determine the effect of profitability on firm value through dividend policy as intervening variable. The population in this study were 133 manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. The data used in this study is secondary data in the form of Corporate Financial Statements that have been published through the Indonesia Stock Exchange. The total sample that meets the criteria in this research is 17 manufacturing companies. The results showed that partially profitability has a positive and significant influence on firm value. Profitability has a positive and significant influence on dividend policy. Furthermore, dividend policy also has a positive and significant impact on company value. In stimulant, profitability variable and dividend policy have significant effect to firm value. Based on the sobel test, it is known that the dividend policy variable as the intervening variable can mediate the relationship between profitability variable and firm value.